2013
DOI: 10.1093/aje/kwt156
|View full text |Cite
|
Sign up to set email alerts
|

Using Pneumococcal Carriage Data to Monitor Postvaccination Changes in Invasive Disease

Abstract: Pneumococcal conjugate vaccines (PCVs) have been introduced worldwide. However, few developing countries have high-quality surveillance systems available for monitoring vaccine impact. We evaluated whether data from nasopharyngeal carriage studies can be used to accurately monitor post-PCV changes in the incidence of invasive pneumococcal disease (IPD) among children under 5 years of age. For various dates during 1991-2010, data on nasopharyngeal pneumococcal carriage and on IPD before and after administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 28 publications
0
60
0
1
Order By: Relevance
“…Our findings conflict with those of most of the studies of carriage in children after the implementation of PCV7 vaccination programmers, which indicate lower carriage rates in vaccinated than in unvaccinated subjects. [1][2][3][4] However, most of these studies were carried out a few months after infant vaccination and in areas in which PCV7 coverage was very high, and the findings probably reflect the immediate direct and indirect effects of PCV7 in subjects who are at relatively low risk of pneumococcal transmission and colonization because of herd immunity secondary to almost universal vaccination. [1][2][3][4] We enrolled school-age children and adolescents who had received the last dose of PCV7 on an average of 6 year before and who were in continuous contact with a large number of unvaccinated contemporaries for all the life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings conflict with those of most of the studies of carriage in children after the implementation of PCV7 vaccination programmers, which indicate lower carriage rates in vaccinated than in unvaccinated subjects. [1][2][3][4] However, most of these studies were carried out a few months after infant vaccination and in areas in which PCV7 coverage was very high, and the findings probably reflect the immediate direct and indirect effects of PCV7 in subjects who are at relatively low risk of pneumococcal transmission and colonization because of herd immunity secondary to almost universal vaccination. [1][2][3][4] We enrolled school-age children and adolescents who had received the last dose of PCV7 on an average of 6 year before and who were in continuous contact with a large number of unvaccinated contemporaries for all the life.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] However, most of these studies were carried out a few months after infant vaccination and in areas in which PCV7 coverage was very high, and the findings probably reflect the immediate direct and indirect effects of PCV7 in subjects who are at relatively low risk of pneumococcal transmission and colonization because of herd immunity secondary to almost universal vaccination. [1][2][3][4] We enrolled school-age children and adolescents who had received the last dose of PCV7 on an average of 6 year before and who were in continuous contact with a large number of unvaccinated contemporaries for all the life. Both of these factors could have conditioned colonization rates in vaccinated children because the protection against colonization offered by PCV7 might have waned over time and the setting of high transmission rates might have favored new colonization's of the same serotypes as those included in the vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Recently, emphasis has been put on the importance of carriage as a proxy measure for PCV impact assessments and for using carriage as an additional and essential biomarker in the licensure pathway of new pneumococcal vaccines. 3,4 A recent systematic review of the direct impact of PCVs by dosing schedules 5 showed consistent reductions in carriage of the serotypes targeted by the vaccine, including a few years after vaccination, with evidence favoring 3-dose schedules over fewer doses. However, systematic estimates of the efficacy of PCVs against carriage and the duration of protection conferred are lacking.…”
mentioning
confidence: 99%
“…2,24,[28][29][30][31] In populations where children have received PCV7, monitoring changes in NP carriage in those <5 y of age has been shown to accurately predict changes in childhood IPD. 32 Moreover, a strong correlation has been established between reductions in NP carriage and IPD in older adults at the individual as well as population level.…”
Section: Pcv7 Vaccination Of Children and Ipd In Older Adultsmentioning
confidence: 99%